Konstruk Identitas Sosial Ulun Lappung dalam Upaya Identifikasi Konflik di Lampung - Setiawan, Wahyu; Sainul, Sainul; Lestari, Aprida Kurnia (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2024)
Social identity is a dynamic, fluid, and multi-faceted reality. Identity formation does not occur linearly but through social processes that are constructed and deconstructed. Ulun Lappung's social identity as an ethnified indigenous community is no exception. Cultural encounters between ethnicities in this area have required Ulun Lappung to redefine its social identity. The process of constructing the social identity of Ulun Lappung in an inter-ethnic context both internally and externally is the main focus of this article. Research data was collected through in-depth interviews with traditional leaders and Lampungese communities in the Sekampung Udik sub-district with a typology of four groups, namely: first, people of different ethnicities in one village but separated in sub-villages; second, different villages but directly adjacent between ethnicities; third, people who are together in one village and sub-villages; and fourth, people who are separated in villages, sub-villages, and even sub-districts. This study urges that the identity construct of Ulun Lappung in inter-ethnic social contestation with migrant communities shows a defensive identity model. No modification, manipulation, or assimilation of identity when they meet in the social sphere with immigrant communities. The inter-ethnic contestation leads Ulun Lappung to form a new identity, called resistance identity.